A systematic review of the early impact of artificial intelligence on higher education curriculum, instruction, and assessment - Liang, Jingjing; Stephens, Jason M.; Brown, Gavin T. L. (Frontiers in Education, 2025)
IntroductionThe emergence of generative artificial intelligence (AI) presents many opportunities and challenges to teaching and learning in higher education. However, compared to student- or administration-facing AI, little attention has been given to the impact of AI on faculty's perspective or their curriculum, instruction, and assessment (CIA) practices.MethodsTo address this gap, we conducted a systematic review of articles published within the first nine months following the release of ChatGPT. After screening following PRISMA statement guidelines, our review yielded 33 studies that met the inclusion criteria.ResultsMost of these studies (n = 17) were conducted in Asia, and simulation and modeling were the most frequently used methods (n = 15). Thematic analysis of the studies resulted in four themes about the impact of AI on CIA triad: (a) generation of new material, (b) reduction of staff workload, (c) automation/optimization of evaluation, and (d) challenges for CIA.DiscussionOverall, this review informs the promising contribution of AI to higher education CIA practices as well as the potential challenges and problems it introduces. Implications for future research and practices are proposed.